Pandemi Covid-19 dalam Penyajian Pelaporan Keuangan dan Keberlangsungan Usaha melalui Prediksi Kebangkrutan - Shinta Budi Astuti; Ameilia Damayanti; Tryas Chasbiandani; Nelyumna Rizal (Postgraduate Program Merdeka University, 2020)
The main purpose of this study is to assess and analyze the business continuity (going concern) of companies before and during the Covid-19 pandemic. The sample of this research is 45 property sector companies listed on the Indonesia Stock Exchange (BEI) for the period 2019-2020 and meet predetermined criteria. This study uses the Altman Z-Score bankruptcy prediction model to assess the business continuity of the sample companies. This research proves that there is indeed an influence from the global Covid-19 pandemic. Companies that are experiencing financial problems and have a strong potential for bankruptcy increased from 2% at the end of 2019 to 51% at the end of June 2020. DOI: https://doi.org/10.26905/afr.v3i2.5451